2012
DOI: 10.1080/16506073.2011.621970
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association Between Emotion Regulation Difficulties and Probable Posttraumatic Stress Disorder Within a Sample of African Americans

Abstract: This study examined the associations between emotion dysregulation and probable posttraumatic stress disorder (PTSD) among 180 African American undergraduates enrolled in a historically black college in the southern United States. Trauma-exposed participants with probable PTSD reported significantly higher levels of overall emotion dysregulation and the specific dimensions of lack of emotional acceptance, difficulties engaging in goal-directed behavior when upset, difficulties controlling impulsive behaviors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 28 publications
10
70
2
Order By: Relevance
“…PTSD, depression, and explosive anger. These findings are consistent with previous research that has indicated that emotion dysregulation is associated with PTSD (Amstadter and Vernon, 2008;Kulkarni et al, 2013;Lilly and Hong Phylice Lim, 2013;Tull et al, 2007;Weiss et al, 2012), and depression following exposure to trauma Klemanski et al, 2012;Lilly and Hong Phylice Lim, 2013), and mediates the relationship between exposure to interpersonal trauma and psychological symptoms Stevens et al, 2013). This is also consistent with studies finding that emotion dysregulation is related to anger and aggression (Besharat et al, 2013;Mauss et al, 2007;Memedovic et al, 2010;.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…PTSD, depression, and explosive anger. These findings are consistent with previous research that has indicated that emotion dysregulation is associated with PTSD (Amstadter and Vernon, 2008;Kulkarni et al, 2013;Lilly and Hong Phylice Lim, 2013;Tull et al, 2007;Weiss et al, 2012), and depression following exposure to trauma Klemanski et al, 2012;Lilly and Hong Phylice Lim, 2013), and mediates the relationship between exposure to interpersonal trauma and psychological symptoms Stevens et al, 2013). This is also consistent with studies finding that emotion dysregulation is related to anger and aggression (Besharat et al, 2013;Mauss et al, 2007;Memedovic et al, 2010;.…”
Section: Discussionsupporting
confidence: 93%
“…Emotion regulation can be defined as the individual's capacity to monitor, evaluate, and modify emotional reactions in a manner that facilitates adaptive functioning (Gratz and Roemer, 2004). Research has indicated that individuals suffering from PTSD have impaired capacity to regulate emotions (Amstadter and Vernon, 2008;Kulkarni et al, 2013;Lilly and Hong Phylice Lim, 2013;Tull et al, 2007;Weiss et al, 2012). Further, difficulties in emotion regulation have been reported to mediate the association between exposure to childhood abuse and symptoms of borderline personality disorder (Gaher et al, 2013) and PTSD (Stevens et al, 2013), as well as between betrayal trauma and symptoms of PTSD, depression, and anxiety .…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, emotional disorders are characterized by the frequent experience of negative emotions (e.g., fear, anxiety, sadness), which in turn are maintained and exacerbated by the use of maladaptive avoidant strategies (e.g., Aldao, Nolen-Hoeksema, & Schweizer, 2010;Tull & Roemer, 2007;Weiss et al, 2012). Although a variety of models exist to explain why NSSI occurs, there is consensus that NSSI is most often used to regulate affect, and more specifically, to reduce or escape from aversive affective states, such as anxiety, sadness, or guilt (Chapman, Gratz, & Brown, 2006;Klonsky, 2007;Nock & Prinstein, 2004.…”
Section: Introductionmentioning
confidence: 97%
“…Higher rates of suicidality in PTSD may be due to the emotion regulation problems which can accompany both PTSD (Weiss et al, 2012) and suicidality. We describe two patients with histories of suicide attempts and primary Axis I diagnosis of PTSD with delayed onset (American Psychiatric Association, 2000), whose suicidality improved significantly after 3-4 weeks of lithium therapy.…”
Section: To the Editormentioning
confidence: 99%